Leveraging stakeholder knowledge in the innovation decision making process. (2016) - Collier, Zachary A.; Trump, Benjamin D.; Wood, Matthew D.; Chobanova, Rossitsa; Linkov, Igor
Organisations must make decisions regarding how to best bridge existing societal challenges or market gaps with innovative technologies and business practices. However, many organisations turn to ad hoc decision-making. Within the contemporary environment of accelerating technological change, this is particularly problematic due to the inability of stakeholders to consider the full breadth of information that must be taken into account during the innovation process, and fosters the potential for inefficient outcomes. We propose an integrated mental modelling and multi-criteria decision analysis framework to provide a structured approach to innovation decision-making. Using formal and transparent decision rules to systematically extract the relevant knowledge from experts, one can efficiently map emergent challenges and assess value tradeoffs associated with competing objectives and investments. This process can assist in the identification of emerging societal, technical, and economic risks, and point to how different types of innovations may resolve such concerns.